The Role of Reading Fluency in Children’s Text Comprehension - Álvarez-Cañizo, Marta; Suárez-Coalla, Paz; Cuetos, Fernando (Frontiers in Psychology, 2015)
Understanding a written text requires some higher cognitive abilities that not all children have. Some children have these abilities, since they understand oral texts; however they have difficulties with written texts, probably due to problems in reading fluency. The aim of this study was to determine which aspects of reading fluency are related to reading comprehension. Four expositive texts, two written and two read by the evaluator, were presented to a sample of 103 primary school children (third and sixth grade). Each text was followed by four comprehension questions. From this sample we selected two groups of participants in each grade, 10 with good results in comprehension of oral and written texts, and 10 with good results in oral and poor in written comprehension. These 40 subjects were asked to read aloud a new text while they were recorded. Using Praat software some prosodic parameters were measured, such as pausing and reading rate (number and duration of the pauses and utterances), pitch and intensity changes and duration in declarative, exclamatory and interrogative sentences and also errors and duration in words by frequency and stress. We compared the results of both groups with ANOVAs. The results showed that children with less reading comprehension made more inappropriate pauses and also intersentential pauses before comma than the other group and made more mistakes in content words; significant differences were also found in the final declination of pitch in declarative sentences and in the F0 range in interrogative ones. These results confirm that reading comprehension problems in children are related to a lack in the development of a good reading fluency.